The bioinformatics analysis and experimental validation of the carcinogenic role of EXO1 in lung adenocarcinoma - Sun, Bohao; Zhang, Jing; Wang, Nan; Zhang, Zhirong; Wu, Yichen; Xie, Mengzhen; Peng, Yanmei; Ye, Yifan; Jiang, Zhaochang; Wei, Shumei (Frontiers in Oncology, 2024)
BackgroundExonuclease 1 (EXO1), a protein involved in mismatch repair and recombination processes, has been identified as a prognostic biomarker in lung adenocarcinoma (LUAD). Nevertheless, its role in LUAD progression remains elusive. This study seeks to elucidate the functional significance of EXO1 in LUAD and evaluate its potential as a therapeutic target.Materials and methodsPatient RNA-seq and clinical data were acquired from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Subsequently, a protein-protein interaction (PPI) network was constructed using differentially expressed genes (DEGs) to identify pivotal genes. Validation of the expression of signature genes was carried out through quantitative real-time PCR (qRT-PCR). Additionally, the association between EXO1 expression and clinical data was investigated. Immunohistochemistry was utilized to assess EXO1 expression in 93 cases of invasive pulmonary adenocarcinoma. Finally, cellular functional assays were conducted to investigate the impact of EXO1 on LUAD cells.ResultsTen key molecules (PBK, ASPM, NCAPG, EXO1, MKI67, RRM2, AURKA, DLGAP5, UBE2C, and CDC6) exhibited significantly elevated expression levels in LUAD tissues. Moreover, elevated levels of EXO1 gene expression correlated strongly with advanced T, N, and M stages and were significantly associated with immune cell infiltration in LUAD. Furthermore, marked increases in EXO1 protein expression were observed in patients diagnosed with invasive pulmonary adenocarcinoma. Notably, patients diagnosed with invasive pulmonary adenocarcinoma who exhibited elevated EXO1 expression levels exhibited increased lymph node metastasis, pleural invasion, poor tumor differentiation, and advanced clinical stage. Additionally, this study employed wound healing assay and CCK-8 cell proliferation assays to investigate the significant role of EXO1 in promoting the growth and migration of lung adenocarcinoma cells.ConclusionsThis study identified ten hub genes associated with the initiation and progression of LUAD. Additionally, EXO1 may serve as a prognostic marker for LUAD patients, offering new perspectives for clinical treatments.